THE CONSTITUTIONAL PRINCIPLE OF SCIENTIFIC DEVELOPMENT BASED ON SOCIAL INTEREST AND THE PATENT LEGAL SYSTEM: THE CASE OF CHAGAS DISEASE - Chein Feres, Marcos Vinício; da Silva, Lorena Abbas; Silva, Alan Rossi (Revista de Direito Brasileira, 2018)
This research adopts a normative political institutional approach, which may empirically contest the constitutional principle of scientific development in accordance with social interest applied to the Brazilian patent legal system, considering the specificities of the case of Chagas disease. Firstly, the theoretical references “living lawfully” and “the struggle for recognition” will be structured as a point of departure for reconstructing the essence of legal methodology that is applied to the case of patent requests concerning Chagas disease. Secondly, a full description of the empirical methodology of analysis is presented, so as to justify every step of the methodological pathway and its implementation, which results in a critical analysis of the legal patent system. Finally, a critique of this system is elaborated, taking into account the analytical process of reasonable descriptive inference provided by the official data extracted from the Brazilian Institute of Industrial Property Rights and converted into cross-referenced tables.